Discovering the causes of mental weakness among conscript soldiers: a sample of qualitative research - Karimi, Alireza; Yousefi, Zahra; Torkan, Hajar (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2022)
Background and Aim: Military service is one of the important steps before entering the working life for many young men in Iran, who usually have many worries about it. Some of the concerns are related to the complaints that other soldiers have about this period. Therefore, this study was to discover the causes of mental weakness of service soldiers. Method: This study was conducted with a qualitative method and thematic analysis method (Clark and Bravan, 2006) in the year 1400-1401 in Isfahan city and in order to answer the question that the causes of mental weakness of conscript soldiers are. The statistical population was all conscript soldiers of Isfahan city, from whom 13 soldiers were selected based on the entry and exit criteria and were interviewed by targeted sampling method. The research tool was semi-structured interview. Results: The collected data were analyzed with the help of thematic analysis. The results showed four main categories: intrapersonal weaknesses (external sources of happiness, high expectations, negative motivation, low self-esteem), family component (causes related to one of the parents and causes related to family conditions), interpersonal causes (weakness communication skills, weakness in managing communication problems) 3) environmental causes (perception of military personnel's weakness in establishing authoritative communication, perception of the environment's indifference to the current needs of soldiers). Conclusion: According to the results, it can be said that a large part of the causes of mental weakness is related to their life history, which can be managed well in the beginning days of military service with the help of increasing skills and awareness. and helped their mental enrichment.